Markets in defense of Europe: Providing public goods in European defense - Lucas Hellemeier; Kaija E. Schilde (EconPol Forum, 2024)
The EU is not yet a defense public goods buyer, but it is generally a public goods provider in the form of the single market, which includes security goods. Public defense goods provision includes a functioning defense market, but the European market for defense equipment remains insufficiently integrated. EU regulation can reduce defense market uncertainty and incentivize R&D spending, ensuring future company competitiveness. The EU should expand its regulatory authority in defense and indirectly provide Europe with a defense market as a public good. Eventually, the EU should work toward consolidating demand and supply, which would further reduce inefficiencies and meet the challenge of secular rises in costs for defense.
Keywords: 330